A termelői és szociális infrastruktúra néhány indikátorának területi kérdései a Nyugat/Vest romániai régióban - Komarek, Levente (Közép-Európai Közlemények, 2009)
This study deals with the territorial aspects of the productive and social infrastructure of the West/Vest Romanian region. The productive infrastructure presents the vehicular traffic, train service, air transport and water carriage situation while the social infrastrucure deals with ducting network, drainage system, gas-main lines, district-heating network and electricity supply issues. In both cases, the study makes a comparison with the national situation.